5t-4=5

Multiply each term in 5t-4=5 by t-4.

5t-4⋅(t-4)=5⋅(t-4)

Cancel the common factor of t-4.

Cancel the common factor.

5t-4⋅(t-4)=5⋅(t-4)

Rewrite the expression.

5=5⋅(t-4)

5=5⋅(t-4)

Simplify 5⋅(t-4).

Apply the distributive property.

5=5t+5⋅-4

Multiply 5 by -4.

5=5t-20

5=5t-20

5=5t-20

Rewrite the equation as 5t-20=5.

5t-20=5

Add 20 to both sides of the equation.

5t=5+20

Add 5 and 20.

5t=25

5t=25

Divide each term in 5t=25 by 5.

5t5=255

Cancel the common factor of 5.

Cancel the common factor.

5t5=255

Divide t by 1.

t=255

t=255

Divide 25 by 5.

t=5

t=5

Solve for t 5/(t-4)=5